(untitled) (Research, Society and Development, 2019)
Recent advances in technology and the media, especially with regard to the use of mobile devices, have increasingly facilitated the lives of people in the most several areas. Such advances have create, for example, new opportunities for the use of technologies in the area of Education, which aims to contribute to the improvement of the teaching and learning process. Tests were conducted in educational environments with the application developed called “QuizApp”, in the sense of making interface improvements and identifying the potentialities and difficulties regarding the use of Mobile resources in the Education area. The results indicate that using the application can improve the teaching-learning process.